Cirque du freak : a living nightmare - Shan, Darren (Boston : Little, Brown, 2000)
Two boys who are best friends visit an illegal freak show, where an encounter with a vampire and a deadly spider forces them to make life-changing choices.
Sequel: The vampire's assistant.
"First published in Great Britain by Collins in 2000"-- T.p. verso.
650
650
Accelerated Reader AR
Keywords: Vampires -- Fiction; Horror stories